1994
DOI: 10.1139/b94-120
|View full text |Cite
|
Sign up to set email alerts
|

Initial litter properties and decay rate: a microcosm experiment on Mediterranean species

Abstract: Twelve leaf litters belonging to 10 Mediterranean species of coniferous and broad-leaved trees and shrubs and grass species were incubated in microcosms in the laboratory at 22 °C and constant humidity for 14 months. Samples were collected at 0.5, 1, 2, 4, 6, 10, and 14 months, the remaining dry weight being measured at each sampling time. At the end of 14 months, the litters had lost between 52 and 74% of their original mass. The comparison of regressions fitted to the various functions showed that for the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 35 publications
5
50
0
9
Order By: Relevance
“…Similarly, Mangenot & Toutain (1980) demonstrated that the litter types that are richest in watersoluble substances are also those that are most quickly decomposed. We have also shown (Gillon et al 1994) that the dynamics of mass loss during the decomposition of 12 Mediterranean litters in microcosms was largely explained by their initial content of water-soluble substances. Prolonged leach ing could therefore transform fresh litter into iForest (2008) 1: 27-33…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Mangenot & Toutain (1980) demonstrated that the litter types that are richest in watersoluble substances are also those that are most quickly decomposed. We have also shown (Gillon et al 1994) that the dynamics of mass loss during the decomposition of 12 Mediterranean litters in microcosms was largely explained by their initial content of water-soluble substances. Prolonged leach ing could therefore transform fresh litter into iForest (2008) 1: 27-33…”
Section: Discussionmentioning
confidence: 62%
“…4A). This pattern suggests that the major effects of litter resources on community structure occur only during the early stages of leaf degradation, when most soluble compounds are leached into the water (e.g., Carpenter 1982b;Gillon et al 1994). Results of the litter manipulation experiment in natural holes ( Fig.…”
Section: Resource Availabilitymentioning
confidence: 96%
“…Individual leaf fragments were progressively smaller from the high quantity treatment to the low quantity treatment. Because the decomposition rate of a leaf is associated with its physical characteristics, such as permeability and thickness (e.g., Gillon et al 1994), the correlation of percent litter remaining with initial litter mass is partly attributed to the greater relative surface area of leaf fragments in the low and medium litter treatments. An alternative explanation is that water in cups containing high litter quantities became saturated with soluble compounds, thereby slowing the rate of leaching.…”
Section: Predator×resource Interactionmentioning
confidence: 99%
“…The mass partitioning of plant cellular material into different pools broadly corresponding to structural classes of biomolecules was attempted in further modelling descriptions (Gillon et al 1994;Liski et al 2005;Adair et al 2008;Incerti et al 2011). These models corresponded to an exponential decay following a first-order kinetics (Olson 1963) and were proved to largely fit experimental decomposition datasets.…”
Section: Originalmentioning
confidence: 99%